Suspended sediment dynamics in macrotidal turbid Hangzhou Bay during Typhoon Chan-hom - Li, Li; Shen, Fangzhou; He, Zhiguo; Yu, Zhuzhu (Frontiers in Earth Science, 2022)
Typhoons are extreme weather events that cause serious social and economic losses in coastal and estuarine areas worldwide. Understanding the impact of typhoons on sediment dynamics is essential for protecting coastal areas from these marine disasters. Hangzhou Bay is macro-tidal, turbid, and frequently affected by strong typhoons. In this study, we established and validated a three-dimensional model coupling waves, current, and sediment to investigate the sediment dynamics in Hangzhou Bay during Typhoon Chan-hom. The results showed that high suspended sediment concentration (SSC) areas during the typhoon were mainly located at the bay head and near the southern shore near the Andong tidal flat. The maximum bottom SSC was at least twice that near the surface. The peak bottom SSC values at the peak flood (6 g/L) were larger than those at the peak ebb (5 g/L) owing to the stronger current velocity at peak flood. The SSC near the northern shore was larger at the peak flood than at other times, and the SSC was high at the southern shore at peak ebb at the cross-section near the Andong tidal flat. The typhoon impacted SSC by changing the bottom stress. SSC was most influenced by wave action, followed by wind stress action, and was least influenced by air pressure action, which contributed 71.3%, 69.9%, and 1.8% to the bottom stress, respectively. Our findings are scientifically important for research on geomorphological evolution and are practically meaningful for coastal management.